GLOBAL CAMPANIAN (UPPER CRETACEOUS) OSTRACOD PALAEOBIOGEOGRAPHY - Seeling J.; Colin J.-P.; Fauth G. (My University, 2004)
The distribution of 218 Campanian marine ostracod genera from 38 geographical areas was used for a quantitative palaeobiogeographical analysis. The data were analysed using multivariate statistical methods, ordination methods and parsimony analysis of endemicity. These methods resulted in distinct geographical area groupings of the studied regions. With these groupings, seven palaeobiogeographical units based on Campanian ostracod occurrences are distinguished. The composition of the area groupings and the distribution of the palaeobiogeographical units are discussed. Their development and spatial distribution are broadly controlled by Campanian palaeoclimates, partly modified by palaeogeographical conditions.
Keywords: Ostracoda; Campanian; Upper Cretaceous; Palaeobiogeography; Multivariate statistics; Ordination methods; Parsimony analysis of endemicity; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Кампанский